Optimizing the search strategy for systematic reviews regarding chronic rhinosinusitis: a Systematic Review - Ana Carolina Soares Ferreira (2022)
Introduction: Chronic rhinosinusitis (CRS) is an inflammatory disease of the paranasal sinuses, affecting 5-12% of the general population. Currently, there is no validated search strategy for CRS. Objective: The aim of this study is to identify and compare the different search strategies used in systematic reviews (SR) regarding CRS and assess their impact on the frequency of manuscripts identified. Methods: We systematically searched Medline, Scopus and Web of science databases from inception to November 13, 2021, for SR about chronic rhinosinusitis. Data regarding search strategy were withdrawn and analyzed. Thereafter sequential combinations of the most used terms were used in simulations to assess the impact on the number of studies identified. Results: Overall, of the 5171 studies identified in the database search, 117 were included for the final analysis. Were identified 224 different search terms across the studies. Search terms ranged between 1 to 49 per SR. The search terms were grouped in 8 categories, where sinusitis and rhinosinusitis were the most used. Conclusion: There was great variability between applied search strategies. Nevertheless, the use of the most common terms namely sinusitis, rhinosinusitis and rhinitis allowed to withdraw a significant number of hits.